How to encourage a lifelong learner? The complex relation between learning strategies and assessment in a medical curriculum. Issue 4 (18th May 2020) - van Woezik, Tamara; Koksma, Jur; Reuzel, Rob; Jaarsma, Debbie; Jan van der Wilt, Gert
Abstract: To foster lifelong learning skills, we need new didactic approaches with aligned assessment methods. Therefore, we investigated whether the outcomes of a project assignment show a different relation to learning strategies than a longitudinal knowledge-based assessment. We studied learning strategies of first year students of medicine and biomedical sciences ( n  = 248) and performed hierarchical regression analyses for the learning strategies and grades of the longitudinal knowledge-based test and project assignment. Scores of students, measured with the Motivated Strategies for Learning Questionnaire (Likert scale 1–7), were relatively low for critical thinking (3.53), compared to rehearsal (4.40), elaboration (4.82), organisation (4.69) and metacognitive self-regulation (4.33). Knowledge based tests showed a significant relation to elaboration ( p  < 0.01). For the project-based assessment, we did not find a significant relation to any learning strategy ( p  = 0.074). Explained variance of the grades was low for all learning strategies ( R 2 < 0.043). Different types of assessment did not discriminate between students with high or low scores on learning strategies associated with lifelong learning. An explanation is that the curriculum is not aligned with assessment, or students do not benefit in terms of grades. We conclude that, if assessment is to drive lifelong learning skills, this is not self-evident.